(3fgGjI GdQGZH dTQM YQhV GHf GdMGLHs - (3LeGd GdOjf YHO GdQMje Hf MSf GdESfhj GdTGaYjs; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s ((3CMeO Hf Ydj GdHdHdSj s)
(3ChdgG (B:s
(3hHYO aEf GdbUjOI GdeSeGI HGdebUO GdLdjd aj Yde GdNdjd fXe GdCSJGP LeGd GdOjf CHj YeQh YKeGf GHf GdMGLH aj Yde GdYQhV hGdbhGaj s
(3BNQgG (B:s
(3hdjS ceG PcQ Hd bO YdeJ eeG SHb EfbSGegeG Edi NGdjf CjVkG hGddg SHMGfg hJYGdi CYde s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdYQhV hGdbhGais